CYTOLOGICAL FEATURES OF THE EPITHELIA OF THE PIG’S GUMS IN THE NORM - Popovych, I.Yu.; Petrushanko, T.A.; Yeroshenko, G.; Zhaga, A.N. (World of Medicine and Biology, 2017)
In the research the features of the cellular composition of the pig's gums were studied. The established tinctorial features of the gingival epitheliocytes in the pigs' cytograms make it possible to classify the gingival mucosa as a masticatory type. The percentage ratio of epithelial cells differs from a similar for a human in the direction of the prevalence of surfical cells in smears (in humans’ cytograms the majority of cells are intermediate epitheliocytes, and the amount of surfical cells is minimal).
Keywords: mucosa of the gums; pigs; cytogram